2020
DOI: 10.1080/23311975.2020.1803579
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in India: A systematic review and synthesis for future research

Abstract: The present study aims to review systematically the state of the art of corporate governance in India. The study uses a sample of 161 published research papers extracted from 101 journals and 17 publishers' databases. The results indicated that 151 studies investigated the board of directors' issues, 90 studies analyzed ownership structure, 64 studies discussed audit committee attributes, and 11 articles studied audit quality. The results provided that among corporate governance issues, board and audit committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 171 publications
(177 reference statements)
0
16
0
Order By: Relevance
“…The relationship between CG and other fields, the results show that financial performance is a major concern in previous studies (Almaqtari, Al-Hattami, Al-Nuzaili, & Al-Bukhrani, 2020). Ishii and Metrick (2003) state that CG in developing countries serves as a major objective in organizational success and can reduce the possibility of financial crises and management conflicts.…”
Section: Introductionmentioning
confidence: 82%
“…The relationship between CG and other fields, the results show that financial performance is a major concern in previous studies (Almaqtari, Al-Hattami, Al-Nuzaili, & Al-Bukhrani, 2020). Ishii and Metrick (2003) state that CG in developing countries serves as a major objective in organizational success and can reduce the possibility of financial crises and management conflicts.…”
Section: Introductionmentioning
confidence: 82%
“… In terms of market capitalization, top companies have been given priority in the selection after considering the above criteria.
Figure 1 Sampling (Source: Almaqtari et al., 2020 , Almaqtari et al., 2020 , Almaqtari et al., 2020 ).
…”
Section: Methodsmentioning
confidence: 99%
“…Further, it is found that greater board independence is associated with more comprehensive statutory and greater disclosure (e.g., Nelson et al., 2010 ; Chen and Jaggi, 2000 ; Owusu-Ansah and Yeoh, 2005 ; Chen and Jaggi, 2000 ; Juhman 2017 ). Different studies also advocate that there is a positive relationship between board independence and different aspects of financial reporting (e.g., Hashed and Almaqtari, 2020 ; Almaqtari & Hashed et al., 2020 ; Farhan et al., 2020 ; Almaqtari & Shamim et al., 2020 ; Almaqtari & Al-Hattami et al., 2020 ; Al Maqtari et al, 2020 ; Farhan et al., 2020 ). Furthermore, Bradbury et al.…”
Section: Empirical Analysismentioning
confidence: 99%
“…While some firm-level factors were consistently associated with disclosure, the results were more mixed when related to corporate governance factors. Almaqtari et al (2020) recently reviewed 161 published articles related to CG in India, their recommendation that the next agenda for research includes the impact of corporate governance on environmental disclosure. Moses et al (2020) concluded that in most developed countries, effective board governance can improve sustainability performance and the quality of the sustainability report, there are mixed conclusions.…”
Section: Corporate Governance Principlesmentioning
confidence: 99%